Samuel Blodget papers - Blodget, Samuel, 1724-1807.
Correspondence, accounts, receipts, lottery tickets, and other business papers, relating chiefly to the construction by Blodget of a canal on the Merrimack River at Amoskeag Falls, N.H., and to lotteries undertaken in New Hampshire and Massachusetts to raise money for the completion of the canal. There are also some papers (1758-1789) relating to the Boston firm of Blodget & Gilman.
Merchant and manufacturer.
Collection material in English.
Keywords: Blodget & Gilman (Boston, Mass.); Canals -- New Hampshire; Lotteries -- Massachusetts; Lotteries -- New Hampshire; Merchants -- Massachusetts -- Boston; Merrimack River (N.H. and Mass.); Industrialists; Merchants